PENGARUH STRATEGI GREEN MARKET ORIENTATION DAN GREEN SUPPLY CHAIN RELATIONSHIP QUALITY DALAM MENINGKATKAN GREEN COMPETITIVE ADVANTAGE - Alhazami, Lutfi; Tobing, Rudy P. (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The manufacturing industry has been particularly highlighted in creating an environmentally friendly supply chain. This is driven by environmentally conscious consumers who recognize the importance of environmental preservation. The pursuit of an eco-friendly supply chain is also motivated by environmental activists' pressure and government policies that regulate environmentally friendly supply chains. Based on these factors, the objective of this research is to examine the influence of Green Market Orientation and Green Supply Chain Relationship Quality on Green Competitive Advantage at PT Aurora World Cianjur. This research adopts a causality approach and collects data through a questionnaire from a sample of 120 respondents, which is then analyzed using multiple regression analysis. The results of this study indicate that there is an influence of Green Market Orientation, Green Supply Chain Relationship Quality, and Green Competitive Advantage. Keywords : Greean Strategy, Market Orientation, Green Supply Chain Relationship Quality, Green Competitive Advantage